2018
DOI: 10.1017/jfm.2018.59
|View full text |Cite
|
Sign up to set email alerts
|

Spatio–temporal analysis of hydrodynamic forces on the particle bed in an oscillatory flow environment

Abstract: A numerical investigation of unsteady hydrodynamic forces on the particle bed in an oscillatory flow environment is performed by means of direct numerical simulations. Statistical descriptions of drag and lift forces for two particle sizes of diameter 372 and 125 in wall units in a very rough turbulent flow regime are reported. Characterization of unsteady forces in terms of spatial distribution, temporal autocorrelation, force spectrum as well as cross-correlations with measurable flow variables is carried ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 62 publications
4
10
0
Order By: Relevance
“…Criteria for incipient motion Having described in detail the cause for turbulence-induced incipient motion, we now focus on assessing different major criteria for the sediment incipient motion in this rolling mode. One of the main difficulties in predicting the onset of incipient motion is determining the critical force above which the sediment starts to roll (Ghodke & Apte 2018). As a first criterion, we use a critical value for the streamwise force based on the moment balance about the contact points of the sediment particle, similar to the method used in Celik et al (2010).…”
Section: Higher Galileo Numbers: Incipient Motion and Rollingmentioning
confidence: 99%
“…Criteria for incipient motion Having described in detail the cause for turbulence-induced incipient motion, we now focus on assessing different major criteria for the sediment incipient motion in this rolling mode. One of the main difficulties in predicting the onset of incipient motion is determining the critical force above which the sediment starts to roll (Ghodke & Apte 2018). As a first criterion, we use a critical value for the streamwise force based on the moment balance about the contact points of the sediment particle, similar to the method used in Celik et al (2010).…”
Section: Higher Galileo Numbers: Incipient Motion and Rollingmentioning
confidence: 99%
“…The TKE budget based on the PIV data obtained in present measurement is analyzed. The production terms included in the TKE budget equation are hereby mainly concerned, including the productions from the streamwise stress P uu and shear stress P uv , which are denoted as [42,43]…”
Section: Production Of Turbulent Kinetic Energymentioning
confidence: 99%
“…Studying roughness-turbulence interactions is one of the motivations of the present study and the TKE budget provides information about the gain or loss of the TKE, as has been examined in the studies considering the effects of roughness or the particle bed on the turbulent flow fields [20][21][22]. In those studies, it was found that the roughness modulates the near-bed turbulence; produces streamwise structures, which undergo distortion and breaking; and reduce the large-scale anisotropy.…”
Section: Tke Budgetmentioning
confidence: 99%